In-Vitro Evaluation of Plant Extracts and Fungicides Against Mycelial Growth of Sclerotium Rolfsii Causing Foot and Root Rot of Betelvine - Rahman, MH; Islam, MR; Aminuzzaman, FM; Latif, A; Rahman, H (Bangladesh Journal of Agricultural Research, 2022)
Betelvine (Piper betle L.) is an important cash crop of Bangladesh. Foot and root rot caused by Sclerotium rolfsii is the most important disease of the crop. It decreases the production of betel leaf to a great extent. Management of the disease, the experiment was conducted to determine the effect of botanical extracts, chemical fungicides and bio-agents on in-vitro mycelium growth of S. rolfsii. Ten fungicides, 11 plant extracts and 2 bio-agents were evaluated. Among the fungicides, 100% inhibition of mycelium growth of S. rolfsii was achieved with the fungicide Provax 200. It was proved to be the best in inhibiting the radial mycelial growth of S. rolfsii. The highest growth inhibition of S. rolfsii was obtained with Garlic clove extract (96.67%) followed by Allamonda (51.12%), and bio-fungicide, Trichoderma harzianum reduced the colony diameter by 56.39% over untreated control. Bangladesh J. Agril. Res. 45(1): 53-64, March 2020